Two Approaches to Cognitive Evaluation: Assessing the Strengths and Limitations of GPCOG and ACE-III - Mąka, Magdalena; Sikora, Dominik; Oleksy, Piotr; Zając, Adam; Zieliński, Karol; Papież, Łukasz; Góralczyk, Ewa; Kamiński, Jakub; Buczkowski, Bartosz (Quality in Sport, 2025)
Introduction The growing elderly population underscores age as a key risk factor for cognitive disorders like dementia. Reliable assessment tools are essential. Addenbrooke’s Cognitive Examination-III (ACE-III) and General Practitioner Assessment of Cognition (GPCOG) are two extensively utilized tools for cognitive assessment. This study compares their sensitivity, specificity, and clinical utility across healthcare settings. Purpose of Research The study evaluates ACE-III and GPCOG for diagnosing dementia such as Alzheimer’s and frontotemporal dementia, focusing on their application in primary care and specialized settings. Materials and Methods This study reviewed 37 publications, including clinical trials and validation studies. Systematic searches in PubMed, NCBI, and Google Scholar used keywords such as “GPCOG,” “ACE-III,” “cognitive screening,” and “dementia.” Results ACE-III demonstrates high accuracy (sensitivity and specificity >93% and 96%) and excels in diagnosing complex dementia. However, its time requirements and need for trained personnel limit its use in resource-limited settings. GPCOG is quick and user-friendly, ideal for primary care but less effective for detailed diagnostics due to its brevity. Conclusions ACE-III is optimal for detailed evaluations in specialized settings, while GPCOG is suited for rapid screening in primary care. Combined, they enhance early detection and management of cognitive disorders.